The fate of the Jews in the early Islamic Near East: tracing the demographic shift from East to West - Lieberman, Phillip I. (Cambridge University Press, 2022)
In this book, Phillip Lieberman revisits one of the foundational narratives of medieval Jewish history-that the rise of Islam led the Jews of Babylonia, the largest Jewish community prior to the rise of Islam, to abandon a livelihood based on agriculture and move into urban crafts and long-distance trade. Here, he presents an alternative account that reveals the complexity of interfaith relations in early Islam. Using Jewish and Islamic chronicles, legal materials, and the rich documentary evidence of the Cairo Geniza, Lieberman demonstrates that Jews initially remained on the rural periphery after the Islamic conquest of Iraq. Gradually, they assimilated to an emerging Islamicate identity as the new religion took shape, sapping towns and villages of their strength. Simultaneously, a small, elite group of merchants and communal leaders migrated westward. Lieberman here explores their formative influence on the Jewish communities of the southern Mediterranean that flourished under Islamic conquest.